A technical and environmental comparison between hydrogen and some fossil fuels. (1st January 2015) - Nicoletti, Giovanni; Arcuri, Natale; Nicoletti, Gerardo; Bruno, Roberto
Highlights: Hydrogen as new non-conventional energy system. Technical and environmental comparison between different type of fuels. Combustion products analysis. Technical and environmental quality indexes for investigated fuels. Proposal of a suitable new energy scenario supplied by hydrogen. Abstract: The exploitation of some fossil fuels such as oil, intended as gasoline or diesel fuel, natural gas and coal, currently satisfy the majority of the growing world energy demand, but they are destined to run out relatively quickly. Beyond this point, their combustion products are the main cause of some global problems such as the greenhouse effect, the hole in the ozone layer, acid rains and generalized environment pollution, so their impact is extremely harmful. Therefore, it is clear that a solution to the energy problem can be obtained only through the use of renewable sources and by means of the exploitation of new low-polluting fuels. In this scenario an important role might be played by hydrogen, which is able to define a new energy system that is more sustainable and cleaner than current systems. For the comparison of the different fuels investigated in this paper, a methodology, which defines appropriate technical and environmental quality indexes, has been developed. These indexes are connected to the pollution produced by combustion reactions and to their intrinsic characteristics of flammability and expansiveness linked to the use of the considered fuels. An appropriate combination of these indexes, in the specific sector of utilization, allows to evaluate a global environmental index for the investigated fuels, highlighting that hydrogen reaches the highest score. In the final part of the paper, a new hydrogen energy economy that would lead to solving the serious environmental problems that damages all the ecosystems of the planet earth, is presented.